ANALISIS KARAKTERISTIK SUDUT PENYEMPROTAN BIODIESEL PALM OIL MELALUI PENAMBAHAN VARIASI KONSENTRASI METANOL - Suryaningrat, Muhammad; Sasongko, Mega Nur; Hamidi, Nurkholis; Saputro, Nurhadi (Jurnal Rekayasa Mesin, 2024)
This study aims to determine the effect of adding methanol as an additive to biodiesel to the spray angle on the diesel fuel injector. The material used in this study was palm oil biodiesel and added methanol with a concentration variation of 5%; 10%; 15%; 20% and 25% of the volume of the mixture (500 mL). The first step is mixing methanol and biodiesel according to the variables (B100; B100M5; B100M10; B100M15; B100M20 and B100M25). Next, the mixture is injected into the simulation of the combustion chamber through the injector nozzle, then the fuel that enters the simulation of the combustion chamber is recorded with a high-speed camera so that an image of the spray angle is obtained. Based on the method that has been carried out, it is found that the addition of variations in the concentration of methanol has an effect on the fuel spray angle. The higher the concentration of methanol added to biodiesel, the greater the spray angle of the fuel mixture. Spray angle for B100; B100M5; B100M10; B100M15; B100M20 and B100M25 are 7.5018o; 10.4018o; 11.8462o; 13.6052o; 14.0148o; and 14.6206o, approximately. This is because with the addition of methanol with higher levels, the mass of oxygen gas will be even greater. The greater the mass of oxygen in the fuel, the easier it is for the fuel to burn.